Cytotoxic hexadepsipeptides and anti-coronaviral 4-hydroxy-2-pyridones from an endophytic Fusarium sp. - Chang, Shanshan; Yan, Biying; Chen, Yuchuan; Zhao, Wuli; Gao, Rongmei; Li, Yuhuan; Yu, Liyan; Xie, Yunying; Si, Shuyi; Chen, Minghua (Frontiers in Chemistry, 2023)
Three new hexadepsipeptides (1−3), along with beauvericin (4), beauvericin D (5), and four 4-hydroxy-2-pyridone derivatives (6−9) were isolated from the endophytic fungus Fusarium sp. CPCC 400857 that derived from the stem of tea plant. Their structures were determined by extensive 1D and 2D NMR, and HRESIMS analyses. The absolute configuration of hexadepsipeptides were elucidated by the advanced Marfey’s method and chiral HPLC analysis. Compounds 4, and 7−9 displayed the cytotoxicity against human pancreatic cancer cell line, AsPC-1 with IC50 values ranging from 3.45 to 29.69 μM, and 7 and 8 also showed the antiviral activity against the coronavirus (HCoV-OC43) with IC50 values of 13.33 and 6.65 μM, respectively.